“Una visión pegada a las pupilas”: perspectivas apocalípticas en la poesía chilena de la crisis (Altre Modernità, 2013)
Drawing from the Apocalypse the idea of a writing devoted to showing, through a revelation, the divine project in the contemporaneity of the community this message is meant for, as the original function of this prophetic genre was, in this essay I aim at studying the testimonial dimension in two Chilean poetry works: El sermón de la montaña (1970) by Raúl Zurita y Diario de navegación (1986) by Tomás Harris. Applying the category of “deictic testimony” I will show how the tension towards a present of crisis (Cold War and inner political conflicts in the first case, dictatorship in the second one) is elaborated in the rhetorical surface and in the enunciation structure of the two texts. As I will show, the direct “indication” of testimony, pointing at a hopeless void, is modulated through the ambiguity and the proliferation of a visionary writing, while the responsibility of enunciation is entrusted to the precarious speech and the obstructed vision of an inept subject.